Fault classification and location for distribution generation using artificial neural networks - Hong F.K.; Keen Raymond W.J.; Heong O.K.; Mei Kuan T. (Institute of Electrical and Electronics Engineers Inc., 2023)
Distributed power generation; Forecasting; Location; Machine learning; Neural networks; Bus networks; Distributed networks; Distribution generation; Fault classification; Fault distance; Fault sections; Location method; Three categories; Complex networks